A voz camoniana no romance Uma viagem à Índia, de Gonçalo M. Tavares - Marques, Carindia do Amarante (2014)
The novel Uma viagem à Índia, by Gonçalo M. Tavares, demonstrates the establishment of dialogues with various texts of world literature, among these are Os Lusíadas, by Luís Vaz de Camões. In this sense, the subject of this study comprises the intertextual relations between the classic by Camões and the contemporary narrative of Gonçalo M. Tavares. The research aims to understand the way in which intertextuality between the two works occurs, verifying the possibility of defining Uma viagem à Índia as a parody of Os Lusíadas. To this end, was sought theoretical shield in the studies of Julia Kristeva (2012) and Laurent Jenny (1979) on the intertextuality as well as the theory of Mikhail Bakhtin (1988, 2013), and Linda Hutcheon (1985 ) on the parody. Furthermore, the work considered the text definitions by Julia Kristeva (2012) and Bakhtin (2003). The methodological approach adopted assumed to analyze important elements of the works studied, in which it was possible to identify intertextual relationship and compare them to the theoretical basis. For this, a qualitative research with exploratory purposes and bibliographical nature was conducted. After the analysis, it was concluded that the novel Uma viagem à Índia takes the classic Os Lusíadas, sometimes repeating it, sometimes deconstructing it, whichever the transformation of meanings. Thus, it is possible to say that the narrative of Gonçalo M. Tavares is a hybrid and dialogic production that, because of the way that resumes the Camões text, may be considered a parody